Peran Barisan Ansor Serbaguna (Banser) dalam Menangkal Radikalisme - Arik Dwijayanto (Farabi, 2019)
The article investigates the phenomenon of intolerance and religious radicalism in Indonesia. Religious radicalism in several regions has shown a critical condition and tends to present takfirism to the other group's religious beliefs. This encourages the Youth Movement of Nahdlatul Ulama (Ansor-Banser) to play an important role in mainstreaming moderate Islam and religious tolerance. Among the research questions asked are how the role of Ansor-Banser in countering religious radicalism?; and how the concept and strategy of Ansor-Banser in mainstreaming moderate Islam in Indonesia.?By using sosiological theory and historical approach, the findings of this research show that Ansor-Banser has three important roles in countering religious radicalism. Firstly, the role in maintaining security and public order with the government apparatus in particular at religious ceremony both organized by muslim community and non muslim. Secondly, the role in reviewing and monitoring the activities of individuals or groups of radical religious dissemination. Thirdly, the role in educating moderate religious values ​​on the younger generation through training activities. Therefore, this research also aims to be a reference in formulating strategic steps for stakeholders especially muslim youth organization to maintain moderate religious understanding and forming religious behavior by relying on Islamic values ​​of tasamuh, tawasuth and tawazun.